Role of YAP/TAZ in bone diseases: A transductor from mechanics to biology - Xin Chen; Xing Ji; Zhaobai Lao; Bin Pan; Yu Qian; Wanlei Yang (Journal of Orthopaedic Translation)
Wolff's Law and the Mechanostat Theory elucidate how bone tissues detect and convert mechanical stimuli into biological signals, crucial for maintaining bone equilibrium. Abnormal mechanics can lead to diseases such as osteoporosis, osteoarthritis, and nonunion fractures. However, the detailed molecular mechanisms by which mechanical cues are transformed into biological responses in bone remain underexplored. Yes-associated protein (YAP) and transcriptional coactivator with PDZ-binding motif (TAZ), key regulators of bone homeostasis, are instrumental in this process. Emerging research highlights bone cells' ability to sense various mechanical stimuli and relay these signals intracellularly. YAP/TAZ are central in receiving these mechanical cues and converting them into signals that influence bone cell behavior. Abnormal YAP/TAZ activity is linked to several bone pathologies, positioning these proteins as promising targets for new treatments. Thus, this review aims to provide an in-depth examination of YAP/TAZ's critical role in the interpretation of mechanical stimuli to biological signals, with a special emphasis on their involvement in bone cell mechanosensing, mechanotransduction, and mechanoresponse.The translational potential of this article: Clinically, appropriate stress stimulation promotes fracture healing, while bed rest can lead to disuse osteoporosis and excessive stress can cause osteoarthritis or bone spurs. Recent advancements in the understanding of YAP/TAZ-mediated mechanobiological signal transduction in bone diseases have been significant, yet many aspects remain unknown. This systematic review summarizes current research progress, identifies unaddressed areas, and highlights potential future research directions. Advancements in this field facilitate a deeper understanding of the molecular mechanisms underlying bone mechanics regulation and underscore the potential of YAP/TAZ as therapeutic targets for bone diseases such as fractures, osteoporosis, and osteoarthritis.